2011
DOI: 10.1007/s10940-011-9134-x
|View full text |Cite
|
Sign up to set email alerts
|

Structural Determinants of Homicide: The Big Three

Abstract: Building upon and expanding the previous research into structural determinants of homicide, particularly the work of Land, McCall and Cohen (1990), the current paper uses county-level data to disentangle three major influences on homicide rates: poverty, racial composition, and the disruption of family structure. Theoretical foundations of these influences are laid out, and the effects of the three factors on homicide rates are tested at two time periods as far removed from one another as possible: 1950-1960 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 68 publications
3
27
0
3
Order By: Relevance
“…With these limitations in mind, the findings hold several key insights for research and theory. First, consistent with the results of prior work, we observed that homicide was more prevalent in disadvantaged areas (Land et al., ; Sampson et al., ; Tcherni, ). In impoverished communities that lack the social capital to attract institutions that promote prosocial values (Kornhauser, ), violence can become an acceptable way to gain status and proactively prevent victimization; individuals may encourage violence as a viable form of conflict resolution; and residents may become desensitized to criminality, including fatal violence (Anderson, ; Furstenberg et al., ; Harding, ; Kirk & Papachristos, ; Wright & Fagan, ).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…With these limitations in mind, the findings hold several key insights for research and theory. First, consistent with the results of prior work, we observed that homicide was more prevalent in disadvantaged areas (Land et al., ; Sampson et al., ; Tcherni, ). In impoverished communities that lack the social capital to attract institutions that promote prosocial values (Kornhauser, ), violence can become an acceptable way to gain status and proactively prevent victimization; individuals may encourage violence as a viable form of conflict resolution; and residents may become desensitized to criminality, including fatal violence (Anderson, ; Furstenberg et al., ; Harding, ; Kirk & Papachristos, ; Wright & Fagan, ).…”
Section: Discussionsupporting
confidence: 92%
“…For example, Sampson, Raudenbush, and Earls (1997) found evidence that concentrated disadvantage predicts violence and homicide, controlling for the effects of collective efficacy (see also Morenoff, Sampson, & Raudenbush, 2001); and Tcherni (2011) found that poverty, race, and divorce rates are robust predictors of homicide rates across U.S. counties and over time. Of the "big three" structural factors, disadvantage has the strongest and most invariant effect on homicide-across locale, time period, and homicide subtypes (Kubrin, 2003;Kubrin & Herting, 2003;Parker, 1989;Tcherni, 2011;Williams & Flewelling, 1988). Even in areas with little variation in disadvantage and in nations with low homicide rates, disadvantage remains the strongest ecological correlate of homicide (Hannon, 2005;Nieuwbeerta, McCall, Elffers, & Wittebrood, 2008;Stults, 2010;Thompson & Gartner, 2014).…”
Section: Community Correlates Of Lethal Violencementioning
confidence: 99%
See 1 more Smart Citation
“…One problem of course is that daily transient population estimates do not exist in most cases. Another downside has to do with the skewed distribution of crime and estimation problems associated with the use of ordinary least-squares (OLS) regression analysis, especially when populations from which the rates are calculated are small (Osgood, 2000;Tcherni, 2011). This is why count data are normally used in these cases.…”
Section: Intra-urban Analysismentioning
confidence: 99%
“…People are unlikely to commit murder to try out their new gun. According to the criminological literature, the major determinants of homicide are structural factors of society such as resource deprivation, racial heterogeneity, social disintegration, and percentage of young people in a population (e.g., Fajnzylber, Lederman, & Loarza, ; Land, McCall, & Cohen, ; McCall, Land, & Parker, ; Tcherni, ). Criminologists present a great deal of empirical evidence that these factors account for substantial variance in homicide rates.…”
Section: Guns and Homicide: A Theoretical Analysismentioning
confidence: 99%